Discipline, Infrastructure, Work Motivation On Employee Performance At Spectrum Billiard & Cafe MalangDiscipline, Infrastructure, Work Motivation On Employee Performance At Spectrum Billiard & Cafe Malang - Nuryana, Ida (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
Human Resource Development is carried out in order to improve employee performance. Human capabilities must be managed by the company and do not come by themselves. Performance is the result of work implementation, namely the implementation of plans carried out by the organization, implemented by leaders and employees who work in the organization, by the government, and by the company (company) to achieve organizational goals. Optimal performance is needed from employees as human resources of the organization to achieve these goals Jufrizen (2021). Quantitative research method multiple linear regression, with a sample size of 50 people. While the results obtained are: Discipline affects the performance of Spectrum Billiard & Cafe Malang employees. Office facilities will affect employee performance at Spectrum Billiard & Cafe Malang Employees. Work Motivation affects employee performance at Spectrum Billiard & Cafe Malang Employees.